First Geoarchaeological and Archaeometric Investigation at the Lucanian (4th–3rd Century BCE) Site of Laurelli (Cilento, Vallo di Diano and Alburni UNESCO Global Geopark—Southern Italy) - Ettore Valente; Antonia Serritella; Maria Luigia Rizzo; Michele Scafuro; Carlo Scirocco; Domenico Guida; Mario Valiante; Chiara Comegna; Giuseppina Balassone; Alberto De Bonis; Celestino Grifa; Elda Russo Ermolli (Geosciences)
The Lucanian site of Laurelli represents one of the largest, still poorly investigated, pre-Roman archaeological sites of the Cilento, Vallo di Diano and Alburni Geopark (southern Italy). The site lies on a large, low-relief surface in the upper portion of the Serrapotamo River basin, a right tributary of the Bussento River. Geomorphological, stratigraphical, archaeobotanical and archaeometric analyses were carried out to understand the following: (1) the choice to settle at the site of the town of Laurelli; (2) the origin of the raw material used to build the town; (3) the vegetation present during the lifetime of the town; and (4) the causes of its abandonment. The results indicate that the site was chosen because it was almost stable from a geomorphological point of view, not being affected by deep landslides. Further investigations are needed to unravel the possible occurrence of flooding as a causative event for the abandonment of Laurelli. Carpinus was widespread and used as a fuel for iron production, but the areas from which the iron was extracted have not yet been discovered. The multidisciplinary approach adopted is suitable for application in other archaeological areas worldwide.